Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a ) ĐKXĐ : \(\hept{\begin{cases}x+1\ne0\\x-1\ne0\\x^2-1\ne0\end{cases}\Rightarrow\hept{\begin{cases}x\ne-1\\x\ne1\end{cases}}}\)
b ) \(P=\frac{2x+3}{x+1}-\frac{x+2}{x-1}+\frac{3x+5}{x^2-1}\)
\(=\frac{\left(2x+3\right)\left(x-1\right)-\left(x+2\right)\left(x+1\right)+\left(3x+5\right)}{\left(x-1\right)\left(x+1\right)}\)
\(=\frac{\left(2x^2+x-3\right)-\left(x^2+3x+2\right)+\left(3x+5\right)}{\left(x-1\right)\left(x+1\right)}\)
\(=\frac{x^2-x}{\left(x-1\right)\left(x+1\right)}=\frac{x\left(x-1\right)}{\left(x-1\right)\left(x+1\right)}=\frac{x}{x+1}\)
Sr còn thiếu
Để \(P\in Z\Leftrightarrow\frac{x}{x+1}=\frac{x+1-1}{x+1}=1-\frac{1}{x+1}\in Z\Rightarrow x+1\inƯ\left(1\right)\)
\(\Rightarrow x+1=\left\{-1;1\right\}\Rightarrow x=\left\{-2;0\right\}\)
\(ĐKXĐ:x\ne\pm1\)
a) \(P=\frac{2x+3}{x+1}-\frac{x+2}{x-1}+\frac{3x+5}{x^2-1}\)
\(\Leftrightarrow P=\frac{\left(2x+3\right)\left(x-1\right)-\left(x+2\right)\left(x+1\right)+3x+5}{\left(x-1\right)\left(x+1\right)}\)
\(\Leftrightarrow P=\frac{2x^2+x-3-x^2-3x-2+3x+5}{\left(x-1\right)\left(x+1\right)}\)
\(\Leftrightarrow P=\frac{x^2+x}{\left(x-1\right)\left(x+1\right)}\)
\(\Leftrightarrow P=\frac{x\left(x+1\right)}{\left(x-1\right)\left(x+1\right)}\)
\(\Leftrightarrow P=\frac{x}{x-1}\)
b) Để \(P\inℤ\)
\(\Leftrightarrow x⋮x-1\)
\(\Leftrightarrow x-1+1⋮x-1\)
\(\Leftrightarrow1⋮x-1\)
\(\Leftrightarrow x-1\inƯ\left(1\right)=\left\{\pm1\right\}\)
\(\Leftrightarrow x\in\left\{0;2\right\}\)
Vậy để \(A\inℤ\Leftrightarrow x\in\left\{0;2\right\}\)